La casa redonda - Erdrich, Louise (Nuevos tiempos (Madrid, Spain), 2013)
When his mother, a tribal enrollment specialist living on a reservation in North Dakota, slips into an abyss of depression after being brutally attacked, 13-year-old Joe Coutts sets out with his three friends to find the person that destroyed his family. Sunday in the spring of 1988, a woman living on a reservation in North Dakota is attacked. The details of the crime are slow to surface as Geraldine Coutts is traumatized and reluctant to relive or reveal what happened, either to the police or to her husband, Bazil, and son, Joe. Increasingly alone, Joe finds himself thrust prematurely into an adult world for which he is ill prepared. While his father, who is a tribal judge, endeavors to wrest justice from a situation that defies his efforts, Joe becomes frustrated with the official investigation and sets out with his trusted friends, Cappy, Zack, and Angus, to get some answers of his own. Their quest takes them first to the Round House, a sacred space and place of worship for the Ojibwe. And this is only the beginning.